Web Based Video Conferencing Application - Tan, Ying En (2021)
As the corona virus moves from a regional epidemic to a global pandemic, businesses and academic institutions have been forced to switch from physical to virtual. Many companies and universities are considering video conferencing as the ideal option for engaging while homes were transformed into classrooms and offices. However, the existing video conferencing system does not allow direct interaction between the participants, the productivity of virtual meeting is comparatively low and there is a lack of a built-in speed test. Therefore, a new web-based video conferencing system is designed and developed to improve team collaboration by providing enhanced engagement. Gamification is used to increase work productivity. It includes a built-in speed test to detect the network connectivity as well as an agenda planner to keep the meeting focused on the topic at hand. Evolutionary Prototyping is adopted to speed up the delivery of the system. Besides, to design a more reliable system, existing similar systems are analysed to define potential features and to integrate into the new system. By using the suggested methodologies and tools, the objectives of this project are accomplished favourably. Moreover, various testing had been performed such as unit, integration, usability testing and user acceptance testing. The web application provides a time-saving agenda planner, a faster and easier built-in speed test, a better collaboration tools and a gamification reward system to boost the engagement. For future work, more important features will be added into this web application such as video recording and virtual background.